Cluster B Personality Disorder Traits as a Predictor of Therapeutic Alliance Over Time in Residential Treatment for Substance Use Disorders. Issue 10 (October 2016) - Olesek, Kyle L.; Outcalt, Jared; Dimaggio, Giancarlo; Popolo, Raffaele; George, Sunita; Lysaker, Paul H.
Abstract : Abstract: While poor therapeutic alliance is a robust predictor of poor outcome in substance abuse treatment, less is known about the barriers to therapeutic alliances in this group. To explore this issue, this study examined whether the severity of cluster B personality disorders predicted therapeutic alliances concurrently and prospectively in a residential substance treatment program for homeless veterans. Participants were 48 adults with a substance abuse disorder. Personality disorder traits were assessed using the Structured Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Personality Disorders, whereas therapeutic alliance was assessed at baseline using the Working Alliance Inventory. Partial correlations controlling for overall symptom severity measured with the Symptom Checklist 90 and education, revealed cluster B traits at baseline predicted all 4 assessments of therapeutic alliance even after controlling for initial levels of therapeutic alliance. Results suggest that higher levels of cluster B traits are a barrier to the formation of working alliances in residential substance treatment.